2020
DOI: 10.1088/1757-899x/736/5/052022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of binary blends poly lactic acid (PLA) and recycled high-density polyethylene (rHDPE)

Abstract: In this work, plastic bottles made of high-density polyethene (HDPE) have been recycled and blended with poly(lactic acid) (PLA). The aim of the work is to prepare a binary blend of PLA and Recycled HDPE (rHDPE) at 90:10 blend ratio by using a twin-screw extruder. The blends were compression moulded and characterized in terms of mechanical and thermal properties. It was found that the rHDPE increased the tensile modulus of the binary blend. Fracture morphology demonstrated that the blend of rHDPE and PLA is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Increasing the PBS content caused a rough fractured surface with large voids and cavities as a result of their incompatibility. This result agrees with Aishah et al [ 67 ], who investigated the recycled HDPE/PLA blend and found that the fracture of the blend formed a rough surface due to completely incompatible recycled HDPE with PLA, subsequently reducing the TS of the binary system. Blends containing 40 and 50 wt.% of PBS portrayed shorter fibrils in contrast to the neat and other blends.…”
Section: Resultssupporting
confidence: 92%
“…Increasing the PBS content caused a rough fractured surface with large voids and cavities as a result of their incompatibility. This result agrees with Aishah et al [ 67 ], who investigated the recycled HDPE/PLA blend and found that the fracture of the blend formed a rough surface due to completely incompatible recycled HDPE with PLA, subsequently reducing the TS of the binary system. Blends containing 40 and 50 wt.% of PBS portrayed shorter fibrils in contrast to the neat and other blends.…”
Section: Resultssupporting
confidence: 92%
“…The recycling and reuse of most commodity polymers have been extensively studied over the years (Satya et al, 2020;Luna et al, 2019a;Luna et al, 2015;Luna et al, 2014;Araújo and Morales, 2018;Ferreira et al, 2019a;Aishah et al, 2020), indicating the feasibility of developing blends between virgin and recycled polymers, in controlled quantities. Meanwhile, blends of poly (lactic acid) and PLA waste from 3D filaments have practically not been investigated in polymer literature, thus leaving a gap to be investigated on the reuse of PLA from additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%